Social Interaction based on Online Media in the use of Transportation - Donal Adrian; Chontina Siahaan (Asian Social Work Journal, 2021)
Online transportation is part of the development of technology that is needed by anyone in carrying out daily activities. This study aims to find out online media-based social interactions in the use of transportation. This research uses qualitative method with observation data collection and in-depth interview. The results showed that the interaction of city people based on online media in using transportation, among others (1) every community is required to be able to use online media, (2) communication conducted in online media discussing about pickup address and destination address, (3) People as consumers can know the amount of payment from the distance traveled through online applications and maps, and (4) the public will give assessment points after receiving transport services online.